Implementasi Pendidikan Karakter Melalui Mata Pelajaran Pendidikan Kewarganegaraan di SMA Jaya Negara Makassar - Suardi Suardi; Herdiansyah Herdiansyah; Herdianty Ramlan; Indah Ainun Mutiara (JED (Jurnal Etika Demokrasi), 2019)
This study aims (1) to find out the implementation of character education, obstacles to the implementation process and solutions to the process of implementing character education through civic education subjects in Makassar State High School. This type of research is qualitative descriptive in the State of Makassar State High School with school head informants, PPKN teachers BK teachers and grade X students at Makassar State High School. The focus of research on the character of discipline, courtesy, hard work, responsibility and honesty in class X in Makassar Jaya State High School. Data sources used are primary data sources in the form of interviews and secondary data sources in the form of documents. Data collection techniques used are interview, observation, and documentation techniques. The results of this study indicate that (1) the implementation of character education through civic education subjects in Makassar State High School is carried out by the teacher through three stages, namely the planning, implementation and assessment stages (2) as for the inhibiting factors experienced by the teacher in implementing character education namely, lack of awareness of students in: obeying rules, student motivation for learning and student awareness of tasks and responsibilities (3) efforts made by the teacher to overcome these obstacles, namely by way of example, set an example for time discipline and obey regulations, giving equal attention to all students and punish students who break the rules.Keywords : Implementation, Character Education, Citizenship Education